New Terrestrial Vertebrate Species Reported for Costa Rica in the Last 10 Years. 2013 to 2024 period (Biocenosis, 2025)
Costa Rica has been characterized for periodically presenting species diversity data. However, there is still a need to gather information that facilitates the understanding and analysis of biodiversity to enhance its conservation and management. This Article presents a compilation of newly reported terrestrial vertebrate species, specifically focusing on amphibians, reptiles, birds, and mammals, between 2013 and October 2024. An extensive bibliographic review was conducted using various sources, including lists of species generated by the Project on Biodiversity in Numbers of the National University of Costa Rica. Among the most relevant findings, there are 78 new species of terrestrial vertebrates classified into 38 families and 60 genera. Of these, 47 records represent range extensions (35 birds, three amphibians, two snakes, and seven mammals), 25 are new species to science (one bird, 15 amphibians, five reptiles, and four mammals), two introduced amphibian species, and the separation of three species was confirmed through morphological and molecular analyses. In terms of distribution, coastal areas such as Puntarenas and Limon show the most records. The specific sites with the newest species are within or very close to Protected Wildlife Areas, such as Coco Island, Tortuguero, and Corcovado.
Keywords: biological diversity; species data; taxonomic groups; geographical distribution; information gaps